PENGARUH NON PERFORMING LOAN DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET MELALUI CAPITAL ADEQUACY RATIO PADA PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2014-2018 - jurnalpps pps; Nurul Khotimah; Nugroho Mardi Wibowo; Chandra Kartika (Jurnal Manajerial Bisnis, 2021)
This study aims to analyze the effect of Non Performing Loan and Loan to Deposit Ratio on Return on Assets through Capital Adequacy Ratio in banking listed in Indonesia Stock Exchange period 2014- 2018. This research is an explanatory research with a quantitative approach. The population in this study are banking companies listed on the Indonesia Stock Exchange. Samples were taken by using purposive sampling technique. The criteria for sampling in this study are banks listed on the Indonesia Stock Exchange which publish bank annual financial reports for 2014-2018 as many as 80. Data analysis in this study used Partial Least Square with the WarpPLS 6.0 program. The results showed that (1) Non Performing Loan has a negative and significant effect on the Bank's Capital Adequacy Ratio, (2) Loan to Deposit Ratio has a negative and significant effect on the Bank's Capital Adequacy Ratio, (3) Non Performing Loan has a negative and significant effect on BankÔÇÖs Return on Assets, (4) Loan to Deposit Ratio has no effect on BankÔÇÖs Return on Assets, (5) Capital Adequacy Ratio has a positive and significant effect on BankÔÇÖs Return on Assets, (6) Non Performing Loan has no effect on Return on Assets through the Bank's Capital Adequacy Ratio, (7) Loan to Deposit Ratio has no effect on the Return on Assets through the Bank's Capital Adequacy Ratio. Keywords: non performing loan, loan to deposit ratio, capital adequacy ratio, return on asset.